Distribution and Migration Patterns of Lead in Atmosphere-tea System by Isotopic Tracing Method - Huabin, Huang; Miaofeng, Yang; Ying, Lin; Nafen, Ke; Yueming, Xiao; Zhixia, Zhuang; Xiaoru, Wang (Plant Diseases and Pests(植物病虫害研究：英文版), 2017)
With low concentration of stable lead isotope as the tracer, using inductively coupled plasma mass spectrometry （ICP-MS）, the lead absorption of tea plants as well as the distribution and migration pattern of lead in plants under different pH environments and spraying introduction of lead sources were studied through pot trial. The results showed that tea plants were very sensitive to atmospheric lead source pollution; atmospheric lead source pollution had a tendency of moving up to the top （bud） ; low pH conditions enhanced lead absorption of plants and promoted upward migration of lead in plants. The experimental method is closer to the actual situation that plants are exposed to low concentration pollution, and could distinguish experimentally introduced lead source from environmentally introduced lead source.